2023
DOI: 10.1186/s12916-023-02765-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of adverse respiratory events with sodium-glucose cotransporter 2 inhibitors versus dipeptidyl peptidase 4 inhibitors among patients with type 2 diabetes in South Korea: a nationwide cohort study

Abstract: Background Impaired respiratory function remains underrecognized in patients with type 2 diabetes (T2D), despite common pulmonary impairment. Meanwhile, there is little data available on the respiratory effects of sodium glucose cotransporter 2 inhibitors (SGLT2i). Hence, we examined the association between SGLT2i use and the risk of adverse respiratory events in a real-world setting. Methods We conducted a population-based, nationwide cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…In addition, there are some data from a South Korean cohort study that shows the benefits of SGLT2i on respiratory events regarding Dipeptidyl peptidase 4 inhibitors, which are another class of oral antidiabetic drugs. 24 SGLT2i might reduce the effects of SARS-CoV-2 on chronic respiratory diseases. One mechanism of SARS-CoV-2 entry into host cells is mainly through angiotensin-converting enzyme 2 (ACE2).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are some data from a South Korean cohort study that shows the benefits of SGLT2i on respiratory events regarding Dipeptidyl peptidase 4 inhibitors, which are another class of oral antidiabetic drugs. 24 SGLT2i might reduce the effects of SARS-CoV-2 on chronic respiratory diseases. One mechanism of SARS-CoV-2 entry into host cells is mainly through angiotensin-converting enzyme 2 (ACE2).…”
Section: Discussionmentioning
confidence: 99%
“…Second, SGLT2is were significantly associated with the decreased risks of several kinds of respiratory disorders (e.g., acute respiratory failure, asthma, and COPD), and infectious disorders (e.g., bronchitis and pneumonia). Similarly, a cohort study ( 34 ) showed that SGLT2is had a significant association with the lower risks of adverse respiratory events including respiratory failure, pulmonary edema, and pneumonia. These findings may suggest that SGLT2is could be used for the prevention of relevant respiratory and infectious diseases.…”
Section: Discussionmentioning
confidence: 90%
“…In a large, national cohort trial, the use of SGLT2 inhibitors was linked with decreased risks of total respiratory events, pneumonia, and respiratory failure among T2DM patients compared to the use of DPP-4 inhibitors [47]. All SGLT2 inhibitor compounds exhibited these respiratory improvements, indicating a possible class effect [47].…”
Section: Benefits and Risks Of Sglt2 Inhibitors On The Pulmonary Systemmentioning
confidence: 98%
“…In a large, national cohort trial, the use of SGLT2 inhibitors was linked with decreased risks of total respiratory events, pneumonia, and respiratory failure among T2DM patients compared to the use of DPP-4 inhibitors [47]. All SGLT2 inhibitor compounds exhibited these respiratory improvements, indicating a possible class effect [47]. In another retrospective cohort analysis of individuals with T2DM in Hong Kong, SGLT2 inhibitor use was linked with a decreased incidence of incident obstructive airway disease (OAD) and a lower rate of OAD exacerbations in clinical settings compared to DPP-4 inhibitors use.…”
Section: Benefits and Risks Of Sglt2 Inhibitors On The Pulmonary Systemmentioning
confidence: 99%